Access to Credit and the Size of the Formal Sector in Brazil - Pablo D'Erasmo (Inter-American Development Bank (IDB), 2013)
This paper studies the link between credit conditions and formalization in Brazil, as both credit and the rate of formalization have notably increased in the last decade. A firm dynamics model with endogenous formal and informal sectors is developed to quantitatively evaluate how much of the change in corporate credit and the size of the formal sector can be attributed to a reduction in the cost of financial intermediation. The model predicts that the observed reduction in intermediation costs generates an increase in the credit-to-output ratio and in the share of formal workers, in line with the data. It is found that -by affecting the corporate interest rate, the allocation of capital and the entry and exit rates- the change in credit conditions has important effects on firm size distribution and aggregate productivity.
Keywords: D24; E26; L11; O16; O17; 330